Analysis and Evaluation Web-Based Sales System Using the ISO 9126 Quality Model - Ryu Tantanu Ryu Tantanu; Verri Kuswanto (Komunitas Dosen Indonesia, 2025)
This study aimed to evaluate the quality of the TR Car Dealership web-based sales system by addressing specific challenges in its functionality, reliability, usability, efficiency, maintainability, and portability. The primary objective was to assess whether the system effectively supports user needs and provides a seamless experience for account registration, product browsing, purchase transactions, and administrative tasks. The ISO 9126 model was utilized as the assessment framework, focusing on six quality attributes that are critical to user satisfaction and system performance. Testing was conducted using black-box testing for functionality assessment and survey-based evaluations for usability and user satisfaction. Automated tools, such as JMeter, Google Lighthouse, and SonarQube, were employed to measure reliability, efficiency, and maintainability under various conditions. The results revealed high scores across several attributes: Functionality achieved an average of 90%, affirming the system’s operational capabilities; Usability scored 91.3%, highlighting ease of use; and Efficiency reached 87%, reflecting effective performance under normal load. However, the Reliability attribute scored 86%, indicating room for improvement, particularly in handling high traffic and unexpected inputs. These findings underscore the TR Car Dealership system’s strengths in user-friendliness and feature completeness while suggesting targeted enhancements for reliability and stability. By addressing these aspects, the system can further enhance user trust and deliver a more resilient and consistent performance. This research demonstrates the effectiveness of the ISO 9126 model in identifying actionable improvements for web-based sales systems.